2010
DOI: 10.1080/13639080903418402
|View full text |Cite
|
Sign up to set email alerts
|

The effects of doing part‐time jobs on college student academic performance and social life in a Chinese society

Abstract: Student employment has been treated as a homogeneous category in studying the effects of doing part-time jobs on student academic performance or social life. In the present study, using data collected from a well-known public university in Macau, we treat student employment as a heterogeneous experience and compare the relative importance of various characteristics of student employment in predicting student academic performance and social life. We find that doing parttime jobs exerts no effect on student acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 33 publications
4
33
0
19
Order By: Relevance
“…This is in line with studies showing that the more hours the students work, the more negative the effect on their grades is (Callender 2008;Bradley 2006). The present study did not confirm previous research showing that work experience within a student's study field was related to a higher grade (Wang et al 2010;Brooks and Youngson 2014). Moreover, some studies have found no relationship between working and grades (Sulaiman and Mohezar 2006;Nonis and Hudson 2006).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This is in line with studies showing that the more hours the students work, the more negative the effect on their grades is (Callender 2008;Bradley 2006). The present study did not confirm previous research showing that work experience within a student's study field was related to a higher grade (Wang et al 2010;Brooks and Youngson 2014). Moreover, some studies have found no relationship between working and grades (Sulaiman and Mohezar 2006;Nonis and Hudson 2006).…”
Section: Discussionsupporting
confidence: 65%
“…Empirical evidence exists of work experience related to one's own academic field increasing students' grade point average (Wang et al 2010). Similar results have been found in research concerning internship (Brooks and Youngson 2014;Patel et al 2012).…”
Section: Introductionsupporting
confidence: 55%
“…There are many reasons for the increase in student employment. Some of the reasons why more students working while attending college are: earning money for covering basic essentials or related expenses (Callender, 2008), relieving the financial burden of parents (Hall, 2010), improving the network with managers, employees, and customers (Curtis, 2007), gaining work experience or practical skills (Wang et al, 2010), supporting a particular lifestyle or as a reaction to peer influence (Oi I & Morrison, 2005), and socializing and meeting people (Curtis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One study suggests that an overwhelming majority of working students consider work to have positively affected their academic performance by improving interpersonal skills, confidence and time management (Curtis, ). Although not explored in our study, the literature also reports the importance of paid work in enhancing employability prospects postgraduation (Callender, ) and increasing students' networking opportunities (Wang, Kong, Shan, & Vong, ).…”
Section: Discussionmentioning
confidence: 99%